Pengembangan Sistem Mading Digital Kampus Berbasis PHP Native dengan Fitur Manajemen Konten dan Keamanan Multi-Level - Aditia, I Dewa Gede Putra; Ramadhani, Desta Erlangga; Sanjaya, I Gede Wahyu (Journal Informatics Nivedita, 2026)
Campus physical bulletin boards have gradually diminished in their effectiveness due to limited information dissemination, lengthy manual updates, and a lack of a structured way to archive content. This research details the creation of a digital bulletin board website for campuses, which utilizes PHP Native and MySQL, and consists of four main operational modules: an admin login system safeguarded against brute-force attacks, a public interface that features automatic filtering for outdated content and protection against SQL Injection, a content management module for administrators that includes upload checks and management of publication dates, and a super-admin data management module that reinforces access control based on user roles. The development of the system adhered to the Waterfall methodology. Black Box Testing was conducted across 23 scenarios spanning all modules by using the Equivalence Partitioning method, resulting in a complete success rate (all 23 scenarios were successful). These findings confirm that PHP Native serves as a robust and secure platform for constructing a multi-tiered digital information system for campuses.